Bioconversion of sugarcane molasses waste to high-value exopolysaccharides by engineered Bacillus licheniformis. (June 2021) - Asgher, Muhammad; Rani, Aneeza; Khalid, Nimrah; Qamar, Sarmad Ahmad; Bilal, Muhammad
Abstract: Exopolysaccharides (EPS) are the large molecular weight carbohydrate polymers extracted from higher plants, algae, fungi and bacteria. EPS produced by bacteria differ from commercial EPS obtained from plants and algae as they have many unique characteristics. This study was designed to develop hyper EPS-producing Bacillus licheniformis mutant using different concentrations of ethyl(methanesulfonate) (EMS). The strain B. licheniformis exposed to 50 μg/mL for 120 min of time durations resulted the highest EPS production (2.855 g/L with 87.3% total carbohydrate content). Herein, to make the bioprocess economical, sugarcane molasses was used as a substrate in fermentation medium. Response surface methodology (RSM) was adapted for optimizational purpose and the mutual effect of various parameters influencing EPS yield was studied. At optimized culture conditions i.e., pH7, temperature 37.5 ​°C, inoculum size 2.5 mL, and 120 h of incubation period, the strain B. licheniformis M4 resulted maximum EPSs production of 9.006 g/L, which was significantly higher than the yield obtained before optimization of fermentation parameters. The improved EPS production by B. licheniformis mutant strain, make it a potential candidate for industrial and biotechnological applications. Graphical abstract: Image 1 Highlights: Genome engineering of B. licheniformis was performed using ethyl(methane sulfonate) mutagen. Improved EPS yield was obtained by engineered microbe using sugarcane molasses substrate. RSM optimization resulted more than 4-folds of EPS yield at specified fermentation parameters.